Peran Fisiologi Dalam Meningkatkan Prestasi Olahraga Indonesia Menuju Sea Games - Danarstuti Utami (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2015)
AbstractNational sport has a considerable influence in strengthening the existence of a nation.Insight into the character and competitiveness is the most important basis for strengtheningenergy in synergy. Sports development is an integral part of the national developmentprocess, particularly in improving the quality of human resources that lead to: (1) an increasein physical health community, (2) mental qualities of spiritual community, (3) the formation ofcharacter and personality of the nation, (4) discipline and sportsmanship, and (5) performanceimprovement that can evoke a sense of national pride.Optimal performance in sports can be achieved when applied quality training andcoaching pramida embraced the concept as a process of achieving goals. Utilization ofscience and technology to obtain information about the physiological characteristics ofathletes, serve as a guide in making the exercise program. More broadly true in improvingachievement and not just one side. Although many facets that contribute to the achievement.It turns out one of the great discipline scientific contribution to the sport is a physiological rolein supporting the improvement of achievement.Keyword : Physiology, sports achievement